Literature Study of Discovery Learning-Based Worksheets for Students' Concept Understanding Skills on Numbers Material (PRISMA, Prosiding Seminar Nasional Matematika, 2023)
In learning mathematics, concept understanding becomes the basis for solving the problems given. However, the lack of a concept investigation guide makes it difficult for students to understand it. So the innovation is needed to guide students in the form of worksheets to help concept understanding through the discovery of ideas. This method is better known as Discovery Learning. The purpose of this study is to analyze student worksheets based on Discovery Learning on the skills to understand on number material. The method used in this research is a literature study where data collection is done by collecting national and international journals related to the research objectives. Based on the results and discussions, it was found that discovery learning-based worksheets can be used as a learning innovation for the concept understanding skills on number material. Furthermore, it is necessary to do further research on the development of discovery learning-based worksheets for concept understanding skills.